The silver swan : [compact disc, unabridged] : a novel - Black, Benjamin, 1945- (Macmillan Audio, 2008)
Two years have passed since the events of the bestselling "Christine Falls", and Quirke, the irascible,formerly hard-drinking Dublin pathologist, ought to know better than to let his curiosity get the best of him.Yet when an acquaintance comes to him about his beautiful young wife's apparent suicide, Quirke's "old itch to cut into the quick of things, to delve into the dark of what was hidden" is roused again.